Effect of Fermentation Duration and Dosage of Eco Enzyme Use on Nutrient Content of Kepok Banana Stem (Musa Paradisiaca L.) - Hasnudi; N. Ginting; Hidayat, Syahrul (Talenta Publisher, 2021)
Kepok banana stems are waste from banana plantation which can be used as an alternative to animal feed. The low crude protein and high fiber are the main problems in Kepok banana stems. Fermentation is one way that can be used to improve the quality of Kepok banana stems. Fermentation used in this study by using Eco enzymes. This research lasted for 3 months starting from July to September 2021 at Compost Center Jl. Biotechnology University of North Sumatra, Laboratory of Nutrition and Animal Feed Animal Husbandry Study Program, Faculty of Agriculture, University of North Sumatra. The research design used was a completely randomized design (CRD) with 3 x 3 factorial pattern with 3 replications, while factor I was various doses of Eco enzymes and factor II was fermentation time. The parameters studied were moisture content and dry matter, crude fat, crude protein, crude fiber, and ash using proximate analysis. Based on the results of the study, it was found that fermentation of Â Kepok banana stems using Eco enzyme at a dose of 5% of the weight of the substrate for 7 days was optimum and efficient in increasing crude protein and reducing crude fiber.